메타데이터의 통합을 위한 스키마 매핑 및 데이터 변환 시스템 - 이민호(Min-Ho Lee); 이원구(Won-Goo Lee); 최윤수(Yun-Soo Choi); 윤화묵(Hwa-Mook Yoon); 송사광(Sa-Kwang Song); 정한민(Han-Min Jung) (韓國컴퓨터情報學會論文誌, 2012)
We devise data conversion methods and implement schema mapping and conversion system based on the study on research paper metadata characteristics analysis. Data conversion in unified form from databases of various systems is necessary for big data analysis. Legacy data conversion systems have drawbacks of syntax dependent problem and inconvenience for use. The implemented system, which is specialized system for research paper metadata, has easy schema mapping interface and can convert data with various syntax. In addition to that, Recompiling of the system is not necessary even if new schema which is not preregistered in the system comes in. We proved its usefulness by usability evaluation. 본 논문에서는 논문 메타 데이터 특성 분석 연구를 토대로 데이터 변환 방법들을 고안하고 스키마 매핑 및 변환시스템을 구현한다. 빅 데이터 분석을 위해서는 다양한 시스템의 데이터베이스에 축적된 데이터를 공통의 형식으로 변환하는데, 현재의 데이터 변환 시스템들은 구문 의존적 문제와 사용의 불편함을 가지고 있다. 본 논문에서 구현된 시스템은 논문 메타데이터 분야에 특화된 시스템으로, 사용하기 쉬운 스키마 매핑 인터페이스를 가지고 있으며 다양한 논문 데이터 구문을 변환할 수 있다. 또한 시스템에 등록되지 않은 새로운 스키마를 가진 데이터가 입력되더라도 시스템의 재 컴파일이 필요 없다. 본 시스템은 사용성 평가를 통하여 시스템 사용성 평균 점수로 89.25점을 받았다.